(untitled) (Journal of Parents and Teachers, 2014)
Drugs such as ecstasy, methamphetamines, or ketamine had a halo of sophistication, as they were designed in laboratories. It seemed that their effects were void ... nothing further from reality. Drug use rates are worrying, especially among youth. It is necessary to act to avoid the consumption of these drugs both at home and in class.